Cationic polymer synergizing with chemotherapeutics and re-purposing antibiotics against cancer cells. (27th January 2021) - Zheng, Yiran; Kng, Jessica; Yang, Chuan; Hedrick, James L.; Yang, Yi Yan
Abstract : A quaternary ammonium-functionalized cationic polymer synergizes with existing chemotherapeutics and re-purposes antibiotics to increase therapeutic efficacy, mitigate toxicity and circumvent drug resistance via its membrane disruption mechanism. Abstract : Chemotherapy is one of the most effective treatments for cancer. However, toxicity and the development of drug resistance have become the major hurdles to the commonly used chemotherapeutics such as doxorubicin and paclitaxel. Antibiotics have also been used as anti-cancer drugs due to their anti-proliferative and cytotoxic effects. However, these anti-tumor antibiotics like ciprofloxacin face the similar resistance and toxicity issues. In this study, we used a quaternary ammonium-functionalized cationic polycarbonate to synergize with the existing chemotherapeutics and re-purpose antibiotics to address the resistance and toxicity issues. When used in combination with the drugs, the cationic polymer induced 2–3 fold more damage in the cancer cell membrane within 2 hours, thus enhancing the uptake of chemotherapeutics up to 2.5 fold more into the breast, liver and even chemotherapeutics-resistant cancer cells. On the other hand, the chemotherapeutics increased the cellular uptake of polymer. The combined effects resulted in 3–10 fold reduction in IC50 of chemotherapy drugs and yielded therapeutic synergy at a clinically-relevant concentration range of drugs when treating multiple types of cancer cells, while the use of guanidinium-functionalized polymer capable of membrane translocation did not lead to a synergistic effect. Thus, the quaternary ammonium-functionalized cationic polymer can increase the therapeutic efficacies of existing drugs, mitigating toxicities by lowering required dosage and circumventing drug resistance via its membrane disruption mechanism. The findings of this study provide insights into designing future anticancer therapy.